The influence of industry affiliation on corporate tax avoidance in Malaysia (Journal of Business Management and Accounting, 2012)
Prior studies on tax avoidance have been emphasising on the individuals behaviour rather than corporations. In addition to this, the available studies on corporate tax avoidance, to date, have been focusing on the developed market while very little attention has been given to the developing countries. Thus, this study attempts to investigate the corporate tax avoidance behaviour in Malaysia, focusing on industry affiliations. Specifically, the objective of this study is to examine the importance of industry affiliations as possible contributions of corporate tax avoidance mechanism. This study documented the link between industry affiliations and corporate tax avoidance in an emerging market. This study tested the relationship by using a crosssectional-time series valuation using panel data analyses, which is Tobit estimations. The results confirmed the importance of industry differences in explaining corporate tax avoidance activity. As more data become available in the future, one could include tax avoidance study in non-listed companies.